STRATEGI PEMASARAN GUNA MENINGKATKAN PENJUALAN SEKTOR INDUSTRI KREATIF KOTA BENGKULU DI MASA PANDEMI COVID 19 - Veny Puspita (Creative Research Management Journal, 2020)
Creatives of bengkulu city in the pandemic time of covid 19. In terms of its nature, this research is descriptive research, namely research that describes certain objects and explains things related to or systematically explains certain facts or frequencies in certain fields factually and careful. This study uses a qualitative descriptive method that leads to a marketing strategy to increase sales of the creative industry sector of bengkulu city during the covid pandemic 19. The data sources in this study were derived from primary data and secondary data. The population in this study were all creative industries. The sampling technique used accidental sampling technique and was analyzed using swot analysis. This kanian is expected to be an input for marketing creative industrial products during a pandemic so that sales will not occur.